Field Station Weather Reports - M. Knapp; E. A. Adee (Kansas Agricultural Experiment Station Research Reports, 2021)
This report includes the annual summary of precipitation from 2020 at the research locations represented in the 2021 field report and further details about the Kansas River Valley locations and the east central Kansas locations.
Keywords: East Central Kansas; Kansas State experiment field; Kaw River Valley; Kansas State Experiment Field; 2020 growing season weather; Kansas weather